Complex obligations under the new civil code - Ioana Nely Militaru (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Complexity obligations is determined by the number of parties involved in the legal obligational or the number of benefits. From this perspective, the work comprises two chapters. The first is the complex obligations plurality of parts, which are obligations: divisible and indivisible solidarity and second chapter complex plurality benefit obligations, which are: main and optional alternative.
Keywords: 330; duty; solidarity; divisibility; indivisibility; alternative duties